The Evaluation of the Application of Fire Extinguisher Installation in the Plastic Sack Industry - Rosita Dwi Lufyana (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Plastic sack industry is an industry that has medium (3) level of fire potential, caused by the material used in the production process is flammable and the industry itself uses electricity to generate heat. In this situation, a protection system is needed in the form of fire extinguisher. By seeing the fire potential in the plastic sack industry, this study aimed to evaluate the installation of fire extinguisher as an effort to prevent and control fire. Method: This study was an observational study through cross-sectional research design. The research samples were 45 fire extinguishers and the variables of the research were fire extinguisher installation process. Result: The classification of fire in the plastic sack industry was A, B, and C. The industry had 45 fire extinguishers spread through the whole production area and office area. It was found that there were three types of fire extinguisher with different capacity on every type, condition, label, height and the sign of installation that still did not comply to the regulation. Conclusion: Fire extinguisher installation in plastic sack industry does not follow the regulations such as procedures of installation and maintenance of fire extinguisher, team of fire prevention, color, the high of installation, condition and placement, label on tube, and marker of fire extinguisher, so it needs to take corrective actions to improve the performance of fire extinguisher when it is used. Keywords:  fire extinguisher, fire extinguisher installation, flammable material, plastic sack, protection system